Work in Progress WIP: Teaching Innovation and Learning that reinforces the Core Subjects of all grades: Mathematics and Natural Sciences - Leal, Jordy Vargas; Santos, Zeila V. T. (2020 IEEE World Conference on Engineering Education (EDUNINE), 2020)
This study will be directed according to the current education provides in recent years in educational institutions. In order to understand and know the difficulties that scientific teachers have to teach Natural Sciences and Mathematics together with the appropriate methodology for students and contact with the experimental part. In many cases, it finds the grade of difficulty that teachers have and how complex it is for them to put into practice their knowledge of the subjects (Mathematics and Natural Sciences) since, according to the research carried out, they are not fully trained to teach the mentioned subjects. The science taught in school should give the student the opportunity to explore their environment and question the phenomena, problems and needs they observe. Achieving in students the opportunities to initiate a process of investigation and solution of problems putting into practice their reasoning capacity